Maneobra a campaign on motorcycles and other transportation options to reduce private car use and alleviate parking problems at the University of the Philippines Diliman - Balanlay, Jerome
Parking is one of the primary challenges that private vehicle users face every day. In UP Diliman, parking has become an increasingly significant issue due to the growing number of students who rely on private cars. The influx of private vehicles within the campus leads to on-street parking and contributes to traffic congestion during peak hours.